Sustainability accounting knowledge and compliance for mining companies in Southern Africa. a bibliometric analysis - Nhorito, Shadreck (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study investigates sustainability accounting compliance and awareness among mining companies in Southern Africa through a bibliometric analysis. It aims to identify enabling factors, challenges, and strategies to strengthen disclosure practices amid environmental degradation, pollution, and climate change. Methodology/approach: A bibliometric approach was applied, analyzing 231 peer-reviewed articles (2000–2024) from Scopus and Web of Science. Data were processed with VOSviewer and Biblioshiny to map publication trends, keyword clusters, author networks, and institutional influence. The analysis was guided by Stakeholder and Institutional Theories to interpret determinants of disclosure. Results/findings: Findings reveal a rapid growth of academic interest, especially after the SDGs, with South Africa leading outputs due to stronger institutions and frameworks such as King IV and JSE integrated reporting. However, sustainability accounting compliance across the region remains fragmented. Adoption of standards like the GRI is uneven, with many firms treating disclosure symbolically. Weak regulation, limited technical capacity, and voluntary frameworks constrain effective implementation. Conclusion: The study demonstrates a gap between academic knowledge and corporate practice in sustainability accounting. Stronger regulation, institutional capacity building, and academic–industry collaboration are essential to embed sustainability reporting into mining operations. Limitations: The reliance on bibliometric data restricts insights into firm-level practices and excludes non-indexed or grey literature. Contribution: This study maps two decades of sustainability accounting research in Southern Africa’s mining sector, providing evidence-based recommendations for regulators, policymakers, and industry leaders to align corporate disclosure with international sustainability standards.